IMPACT OF FINTECH REGULATIONS ON SPAYLATER OPERATIONS AS WELL AS A REVIEW OF SPAYLATER CONSUMER PROTECTION LAWS - M Raihan Noer; Senta Rina Damanik; Roni Sianturi .; Bonaraja Purba .; Khairul Adli Batubara (Politeknik Bisnis Indonesia, 2024)
This research aims to see the impact of fintech regulations on Shopee Paylater online loan operations as well as studying consumer protection laws in Shopee Paylater services. The method used in this research is the normative legal method, namely a research approach that focuses on the norms or legal regulations that apply and must be obeyed by society. The results of the analysis show that Financial Technology operates under the auspices of the central bank, namely Bank Indonesia, while also being supervised by applicable laws. The law that oversees financial technology is Law no.4 of 2023 concerning Development and Strengthening of the Financial Sector which regulates the financial technology industry. This law is the latest instrument in dealing with increasingly developing fintech. One type of Fintech that is popularly used by people today is Shopee Paylater. Fintech developments such as Shopee Paylater can also raise problems related to consumer protection. Therefore, the importance of regulations in consumer protection. The law that regulates consumer protection is Law Number 8 of 1999 concerning Consumer Protection. There are also policies or efforts that have been made by the government related to consumer protection, namely by establishing a Financial Services Authority.